1991
DOI: 10.1038/bjc.1991.235
|View full text |Cite
|
Sign up to set email alerts
|

Multiple epitopes of the human ovarian cancer antigen 14C1 recognised by human IgG antibodies: their potential in immunotherapy

Abstract: Summary We have defined a novel ovarian cancer-associated membrane antigen, 14C1, using human monoclonal antibodies derived by EBV-transformation of in situ sensitised patients' B-cells. The pattern of recognition of this antigen by these antibodies suggests that at least three epitopes are discernable. These antibodies can be used to promote the in vitro killing of ovarian cancer cells by activated macrophages and cytokines, implying a role for this antigen in the immunotherapy of ovarian malignancies. Eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Immunogenic tumor-associated antigens have been described primarily for malignant tumors including melanoma, breast cancer, colon cancer, ovarian cancer (Real et al, 1988;Ben-Mahrez et al, 1990;Gallagher et al, 1991;Disis et al, 1994;Disis and Cheever, 1996;Boon and Lloyd, 1997). However, dierent studies have indicated that meningiomas are also capable of inducing an immune response in the host.…”
Section: Introductionmentioning
confidence: 99%
“…Immunogenic tumor-associated antigens have been described primarily for malignant tumors including melanoma, breast cancer, colon cancer, ovarian cancer (Real et al, 1988;Ben-Mahrez et al, 1990;Gallagher et al, 1991;Disis et al, 1994;Disis and Cheever, 1996;Boon and Lloyd, 1997). However, dierent studies have indicated that meningiomas are also capable of inducing an immune response in the host.…”
Section: Introductionmentioning
confidence: 99%